Performance evaluation of directly fastened asphalt track using a full-scale test. (15th June 2016) - Lee, Seong-Hyeok; Choi, Yeong-Tae; Lee, Hyun-Min; Park, Dae-Wook
Abstract: Asphalt concrete has never been used in railroad trackbeds in South Korea. In this study, full-scale testing was conducted to evaluate the performance of asphalt concrete mixtures developed for use in railroad trackbeds. Asphalt trackbeds of three thicknesses were constructed at full scale and subjected to static loading. Measurements of earth pressure, strain, and displacement indicate that a thickness of approximately 30 cm is appropriate for an asphalt trackbed subjected to train loadings. In addition, the measurements provide information on the behavior characteristics of asphalt trackbeds.